Inhibition of PI3Kδ Enhances Poly I:C-Induced Antiviral Responses and Inhibits Replication of Human Metapneumovirus in Murine Lungs and Human Bronchial Epithelial Cells - Fujita, Akitaka; Kan-o, Keiko; Tonai, Ken; Yamamoto, Norio; Ogawa, Tomohiro; Fukuyama, Satoru; Nakanishi, Yoichi; Matsumoto, Koichiro (Frontiers in Immunology, 2020)
Viral infections of the airway can exacerbate respiratory diseases, such as asthma or chronic obstructive pulmonary disease (COPD), and accelerate disease progression. Phosphoinositide 3-kinase (PI3K)δ, a class 1A PI3K, has been studied as a potential target for achieving anti-oncogenic and anti-inflammatory effects. However, the role of PI3Kδ in antiviral responses is poorly understood. Using a synthetic double-stranded RNA poly I:C and a selective PI3Kδ inhibitor IC87114, we investigated the role of PI3Kδ signaling in poly I:C-induced expression of the T lymphocyte-inhibitory molecule programmed death 1 ligand 1 (PD-L1), inflammatory responses and antiviral interferon (IFN) responses. C57BL/6N mice were treated with IC87114 or vehicle by intratracheal (i.t.) instillation followed by i.t. administration of poly I:C. Poly I:C increased PD-L1 expression on epithelial cells, lymphocytes, macrophages and neutrophils in the lungs and IC87114 suppressed poly I:C-induced PD-L1 expression on epithelial cells and neutrophils possibly via inhibition of the Akt/mTOR signaling pathway. IC87114 also attenuated poly I:C-induced increases in numbers of total cells, macrophages, neutrophils and lymphocytes, as well as levels of KC, IL-6 and MIP-1β in bronchoalveolar lavage fluid. Gene expression of IFNβ, IFNλ2 and IFN-stimulated genes (ISGs) were upregulated in response to poly I:C and a further increase in gene expression was observed following IC87114 treatment. In addition, IC87114 enhanced poly I:C-induced phosphorylation of IRF3. We assessed the effects of IC87114 on human primary bronchial epithelial cells (PBECs). IC87114 decreased poly I:C-induced PD-L1 expression on PBECs and secretion of IL-6 and IL-8 into culture supernatants. IC87114 further enhanced poly I:C- induced increases in the concentrations of IFNβ and IFNλ1/3 in culture supernatants as well as upregulated gene expression of ISGs in PBECs. Similar results were obtained in PBECs transfected with siRNA targeting the PIK3CD gene encoding PI3K p110ẟ, and stimulated with poly I:C. In human metapneumovirus (hMPV) infection of PBECs, IC87114 suppressed hMPV-induced PD-L1 expression and reduced viral replication without changing the production levels of IFNβ and IFNλ1/3 in culture supernatants. These data suggest that IC87114 may promote virus elimination and clearance through PD-L1 downregulation and enhanced antiviral IFN responses, preventing prolonged lung inflammation, which exacerbates asthma and COPD.